72.9k views
2 votes
Given that f(x)=x+1 and G(x)=x^2-x, find (f+g)(-6)

User Hdomos
by
5.6k points

1 Answer

2 votes

Answer:

(f + g)(-6) = 37

Explanation:

Points to remember

If f(x) and g(x) be the two functions, then

(f + g)(x) = f(x) + g(x)

It is given that, f(x) = x + 1 and g(x) =x^2 - x

To find the value of (f + g)(-6)

(f + g)(-6) = f(-6) + g(-6)

f(x) = x + 1

f(-6) = -6 + 1 = -5

g(x) =x^2 - x

g(-6) = (6)^2 - (-6)

= 36 + 6 = 42

(f + g)(-6) = -5 + 42 = 37

User Whatupdave
by
5.7k points